ANEMIA CALON PENGANTIN (CATIN) DAN TRIMESTER 1 SEBAGAI FAKTOR RESIKO KEK PRIMIGRAVIDA DI PUSKESMAS PRAMBONWETAN TUBAN - Erna Eka Wijayanti; Nurus Safaah; Miftahul Munir; ilmiatus qoyimah (Jurnal Kebidanan, 2026)
Nutritional deficiency during pregnancy can lead to Chronic Energy Deficiency (CED) and stunting. In Indonesia, the high rate of anemia among women of childbearing age significantly contributes to this nutritional crisis. This study aims to analyze the relationship between anemia during the preconception period (catin) and the first trimester of pregnancy with the incidence of CED in primigravida pregnant women at the Prambonwetan Community Health Center, Tuban. This quantitative study employed a cross-sectional design. Samples were selected using simple random sampling via random.org. The independent variables were anemia during the catin period and the first trimester, while the dependent variable was the incidence of CED in primigravida mothers. Data were gathered from medical records, catin registers, and integrated ANC books, then analyzed using the Spearman's rank correlation via SPSS version 26. The Spearman’s rank test analysis revealed a significant relationship, with a value of P < 0,001, leading to the rejection of $H_0$ and acceptance of $H_1$. Statistically, there is a strong correlation between anemia during the catin period and first-trimester pregnancy with the incidence of CED in primigravida mothers. Anemia experienced during both the preconception stage and early pregnancy is significantly associated with the occurrence of CED in first-time pregnant women. Pregnant women and future brides are strongly encouraged to consume balanced nutrition and routinely take blood supplement tablets (Fe) to prevent anemia and lower the risk of CED